In-Plant Protection against Helicoverpa armigera by Production of Long hpRNA in Chloroplasts - Bally, Julia; McIntyre, Glen J.; Doran, Rachel L.; Lee, Karen; Perez, Alicia; Jung, Hyungtaek; Naim, Fatima; Larrinua, Ignacio M.; Narva, Kenneth E.; Waterhouse, Peter M. (Frontiers in Plant Science, 2016)
Expressing double-stranded RNA (dsRNA) in transgenic plants to silence essential genes within herbivorous pests is referred to as trans-kingdom RNA interference (TK-RNAi) and has emerged as a promising strategy for crop protection. However, the dicing of dsRNA into siRNAs by the plant’s intrinsic RNAi machinery may reduce this pesticidal activity. Therefore, genetic constructs, encoding ~200nt duplex-stemmed-hairpin (hp) RNAs, targeting the acetylcholinesterase gene of the cotton bollworm, Helicoverpa armigera, were integrated into either the nuclear or the chloroplast genome of Nicotiana benthamiana. Undiced, full-length hpRNAs accumulated in transplastomic lines of N. benthamiana and conferred strong protection against H. armigera herbivory while the hpRNAs of nuclear-transformed plants were processed into siRNAs and gave more modest anti-feeding activity. This suggests that there is little or no RNAi machinery or activity in the chloroplast, that hpRNAs produced within this organelle do not enter the cytoplasm, and that oral delivery of chloroplast-packaged intact hpRNA is a more effective means of delivering TK-RNAi than using nuclear encoded hpRNAs. This contrasts with a recently reported correlation between siRNA expression and effectiveness of TK-RNAi targeting the chitinase gene of H. armigera, but is consistent with reports of efficient TK-RNAi by dsRNA generated in chloroplasts by converging promoters flanking a pest gene sequence, and from very small (21nt-stem) hpRNAs resembling artificial miRNAs. Here we demonstrate that hpRNAs, constructed along the conventional design principles of plant RNAi constructs, but integrated into the chloroplast genome, are stable and effective over multiple generations and hold the promise of providing durable pest resistance in crops.